Analisis Dampak Perilaku Fear of Missing Out (FoMO) Di Kalangan Pengguna Media Sosial - Latief, Rahmawati (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam, 2024)
Fear of Missing Out (FoMO) behavior is a dark side effect of excessive and undirected social media use. This study aims to curate, analyze and synthesize knowledge about the negative impact of FoMo behavior among social media users. The method used is a systematic literature review which is often abbreviated as SLR by researching 14 empirical research articles obtained from the google scholar database with a time span of 2018 to 2024. The results of the study found eleven negative impacts of FoMO behavior which generally hit vulnerable groups, namely groups of people aged teenagers and students who are generation Z.